2018
DOI: 10.1039/c7cp06344j
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent hydrolysis of supported planar lipids was triggered by honey bee venom phospholipase A2with the right orientation at the interface

Abstract: Hydrolysis of planar phospholipids catalyzed by honey bee venom phospholipase A (bvPLA) was studied. Experiments demonstrated that Ca ions mediated between the lipids and bvPLA, induced reorientation of bvPLA, and activated hydrolysis. One of the hydrolysis products, fatty acids, was desorbed, and the other one, lysophospholipids, self-organized at the interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 28 publications
2
21
2
Order By: Relevance
“…Here in particular, the secondary signal was chosen to be a poison for the receiver GUV so that a predator–prey relationship was established between the two GUV populations. The predator GUVs were loaded with membrane impermeable Ca 2+ ions, which upon transfer through the α-HL pores to the prey GUV activate the phospholipase A 2 (PLA 2 ) , and lead to a fluorescent signal coming from the calcium sensitive dye, Rhod2. Finally, the calcium activated PLA 2 cleaved the fatty acid tail of the phospholipid in the prey GUVs and caused to their collapse.…”
Section: Resultsmentioning
confidence: 99%
“…Here in particular, the secondary signal was chosen to be a poison for the receiver GUV so that a predator–prey relationship was established between the two GUV populations. The predator GUVs were loaded with membrane impermeable Ca 2+ ions, which upon transfer through the α-HL pores to the prey GUV activate the phospholipase A 2 (PLA 2 ) , and lead to a fluorescent signal coming from the calcium sensitive dye, Rhod2. Finally, the calcium activated PLA 2 cleaved the fatty acid tail of the phospholipid in the prey GUVs and caused to their collapse.…”
Section: Resultsmentioning
confidence: 99%
“…With the help of molecular dynamics in combination with mass spectrometry, it was shown that the lipid membrane works as an allosteric activator for sPLA2 [8]; binding to the membrane leads to conformational changes and activates the enzyme [9]. Using a combination of confocal microscopy and IR spectrometry, it was shown that calcium ions can be involved in the binding of sPLA2 to the membrane surface [10]; calcium ions can orient protein molecules on the membrane surface and activate the enzyme. Moreover, fluorescence microscopy and atomic force microscopy studies revealed that changes in the membrane structure caused by sPLA2 lead to an increase in the amount of adsorbed protein, that is, to the formation of new lipid binding sites for sPLA2 [11].…”
Section: Short Communicationmentioning
confidence: 99%
“…Measuring the direct effect of phospholipases on lipid bilayers using such impedance measurements has also been described, but the techniques require a time-consuming lipid bilayer deposition methodology or include the use of toxic solvents such as chloroform . Likewise, other techniques such as the use of a quartz crystal microbalance, sum-frequency generation vibrational spectroscopy measurements, and atomic force microscopy have been used to study the mechanistic properties of PLA isoforms on lipid bilayers, but they also rely on lengthy substrate deposition methodologies. To the best of our knowledge, most phospholipase biosensor designs are also incapable of rapidly distinguishing between phospholipase isoforms such as phospholipase A 1 (PLA 1 ) and phospholipase A 2 (PLA 2 ).…”
Section: Introductionmentioning
confidence: 99%